2019
DOI: 10.9787/kjbs.2019.51.3.201
|View full text |Cite
|
Sign up to set email alerts
|

Development of EST-SSR Markers for Cultivar Determination and Genetic Diversity Studies of Commercial Chrysanthemums in the Korean Floral Market

Abstract: Chrysanthemum morifolium Ramat. is one of the major flowering crop plants worldwide. However, domestic chrysanthemum markets have recently faced a downturn. To stimulate related industries, breeding technologies and efficient protection systems using molecular markers must be established. However, high cost and intensive efforts are required to develop useful molecular markers for the chrysanthemum as it is a polyploid crop with highly complex genome organization. Thus, the aim of this research was to develop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…These six SSR markers generated 2 to 6 alleles with an average of 3.5 alleles per locus. The allele number per SSR locus is comparable with other results reporting an average of 2.7 alleles and 5.6 alleles per locus in 11 and 147 varieties of chrysanthemum tested with 7 and 14 SSR markers, respectively [29,30]. The degree of polymorphism (PIC) for the 57 white chrysanthemum cultivars with respect to six SSR markers was an average of 0.53, which is similar to that related in previous reports for chrysanthemum cultivars.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These six SSR markers generated 2 to 6 alleles with an average of 3.5 alleles per locus. The allele number per SSR locus is comparable with other results reporting an average of 2.7 alleles and 5.6 alleles per locus in 11 and 147 varieties of chrysanthemum tested with 7 and 14 SSR markers, respectively [29,30]. The degree of polymorphism (PIC) for the 57 white chrysanthemum cultivars with respect to six SSR markers was an average of 0.53, which is similar to that related in previous reports for chrysanthemum cultivars.…”
Section: Discussionsupporting
confidence: 90%
“…Analysis of genetic identity among the varieties is useful for the protection of breeders' intellectual property rights. The standard chrysanthemum varieties Pingpong and White Runner have shown higher degrees of genetic similarity that preclude discrimination [30]. In contrast, Feng et al [41] reported a genetic distance of 0.97, proving the higher genetic diversity of the tested cultivars and confirming the effectiveness of the SSR markers.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation